EFFECT OF ACADEMIC STAFF UNION OF UNIVERSITIES STRIKE ON THE PSYCHOSOCIAL WELLBEING OF UNDERGRADUATES IN LAGOS STATE, NIGERIA - Omozusi Mercy Omosefe; William Oluwaseyi Emmanuel; Joy Tinuade Adeyanju (International Studies Journal)
Education is necessity for the proper development of both individuals in particular and the nation at large. However, recurring strikes of ASUU has not being without detrimental effects and consequences whether to the students or to the union members themselves. This study examined the effect of ASUU strikes on the psychosocial well-being of university students in Nigeria.A descriptive survey research design was adopted for the study and the target population were undergraduate students of University of Lagos. A simple random sampling was used to select 396 students as respondents for the study. A self-developed questionnaire was employed as the research instrument. The research questions were answered using descriptive statistics of frequency, percentage, mean and standard deviation. The result showed that the respondents disagree that ASUU strike has an effect on the emotional well-being of students (average mean 2.45 and SD=1.015). They also disagreed that the ASUU strike had an effect on their mental status (average mean 2.32 and SD=1.02). It was also found that the respondents agreed that ASUU strike had an effect on their social actualization (average mean 2.60 and SD=.95) and  also affected their personal growth as students (average mean 2.64 and SD=.97). The study recommended that there is need for ASUU to find alternative method of registering their grievances and expectations from the government.  There is also the need for government to put the well-being of affected students into consideration in their negotiation with ASUU, in order to avoid future occurrence of strikes.